Continuous measurement of suspended sediment concentration: Discussion of four techniques. (July 2016) - Felix, David; Albayrak, Ismail; Boes, Robert M.
Graphical abstract: Monitoring of Suspended Sediment Concentration (SSC). Turbidimeters. Acoustic method (single-frequency attenuation). Laser In-Situ Scattering and Transmissiometry (LISST). Vibrating tube densimetry (Coriolis Flow- and Density Meter). Gravimetric analysis of bottle samples (as reference). Highlights: Turbidimeters and single-frequency acoustics are sensitive to varying particle size. LISST provides suspended sediment concentrations (SSCs) and particle sizes. LISST measurements are not or less biased by variations of particle sizes. Vibrating tube densimetry is suitable to measure higher SSCs. Site- and task-specific combinations of measuring techniques are recommended. Abstract: Continuous measurements of suspended sediment mass concentration (SSC) and particle size distribution (PSD) in surface waters and hydraulic schemes are of prime importance for the investigation and management of many fine-sediment related processes. In this paper, the performance of selected techniques and instruments for continuous SSC measurements is discussed based on results of a field study and a recent literature-review paper. SSCs measured with Laser In Situ-Scattering and Transmissometry (LISST) or vibrating tube densimetry were confirmed to be not or less biased by temporary PSD variations than SSCs obtained from turbidimeters or a single-frequency acoustic attenuation method. Vibrating tube densimetry allowed measurements of higher SSCs (e.g. 10 g/l) compared to the other investigated instruments. For the conversion of the instruments' outputs to SSC, i.e. calibration, and for validation, gravimetric analysis of bottle samples is recommended as reference.